Atomistic scale insight to investigate the strain rate effect on mechanical response of boron nitride nanosheet reinforced nanocomposites. (2022) - Chaurasia, Ankur; Kumar Singh, Sandeep; Parashar, Avinash
Abstract: In this research article, atomistic simulations were employed to evaluate the strain rate effect on the mechanical properties of h-BN/HDPE nanocomposites. The atomistic modeling-based approach, in conjunction with a reactive force field (Reaxff) potential, was used to calculate the mechanical properties of the h-BN/HDPE nanocomposites at different strain rates. In order to capture the non-bonded interaction between h-BN nanosheet (reinforcement) and HDPE (matrix), L-J potential parameter was used. Mechanical properties such as ultimate tensile strength and failure strain of h-BN/HDPE were predicted in the strain rate range of 10 8 s −1 to 10 10 s −1 . It was revealed from the simulations that yield strength and elastic modulus are strongly dependent on the strain rate loading. It was reported that the yield strength of the h-BN/HDPE nanocomposites increases with the strain rate. Apart from this study, the authors have also investigated the strain rate effect on the mechanical behaviour of pristine HDPE and compared it with the mechanical response of h-BN/HDPE nanocomposites at the same strain rate loading.